THE POSSIBILITY OF USING EXISTING METHODS FOR DRYING ROAST MEAT - Skrypnyk, V.; Ponomarenko, B. (Scientific Progress & Innovations, 2022)
Technology related to the food industry is constantly improving and becoming more efficient. Consumers today choose high quality food products with a long shelf life. In Ukraine, where during the war with russia there is an acute issue of food supply in the areas of combat operations as well as in areas where efforts are being made to overcome a humanitarian disaster, food products of long-term storage are in high demand. One way of meeting the nutritional needs of such conditions is to provide tinned and dried foodstuffs and, above all, meat products that have a long shelf life and do not require special conditions for such storage. The production of these food products under wartime conditions requires minimal loss of raw materials, energy consumption and production time. In the food industry, the drying process is used to preserve raw materials, including meat, to extend their shelf life. The meat drying process is accompanied by the removal of moisture from the material into its surface layers and its subsequent removal in the form of liquid or vapour by the drying agent. Dried products, including dried fried meat, can be useful for military personnel on the front line, internally displaced persons, journalists, etc. To date, there is a lack of information on how to dry fried meat. The relevance of this issue is that meat is in considerable demand among consumers. The article aims to summarise and systematise the current understanding of the methods of drying food raw materials, the existing equipment for their implementation and to find a possible development of the drying process of fried meat. The article compares the efficiency of the drying methods with the possibility to use them for drying fried meat. It has been found that fried meat can be obtained by convection, sublimation, conduction and natural methods. The conductive method has limited use for drying food raw materials, but can be effective for drying fried meat due to its high heat transfer index, short drying process duration and low specific energy consumption.